2015
DOI: 10.1111/jsbm.12188
|View full text |Cite
|
Sign up to set email alerts
|

Networks, Entrepreneurial Orientation, and Internationalization Scope: Evidence from Chilean Small and Medium Enterprises

Abstract: During the last twenty years the literature on internationalised small firms discussed at length the speed of internationalisation, illustrating the importance of born globals.The geographic scope of small firm internationalisation and its implications for international business and entrepreneurship theories have however been overlooked, especially with regards to firms based in Latin America. This study expands the research agenda on the effects of networks and entrepreneurship orientation for the internation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(140 citation statements)
references
References 80 publications
(176 reference statements)
7
121
0
12
Order By: Relevance
“…On the other hand, some of the studies found either no or mix relationship between EO and SME export performance (Feder, 2015;Felzensztein et al, 2015;Frishammar & Andersson, 2009). However, there is a variation in previous studies' findings.…”
Section: Mediating Role Of Tqm Between Eo and Sme Export Performancementioning
confidence: 99%
“…On the other hand, some of the studies found either no or mix relationship between EO and SME export performance (Feder, 2015;Felzensztein et al, 2015;Frishammar & Andersson, 2009). However, there is a variation in previous studies' findings.…”
Section: Mediating Role Of Tqm Between Eo and Sme Export Performancementioning
confidence: 99%
“…Os primeiros passos na internacionalização são considerados uma inovação na empresa (REID, 1981), mas tal esforço implica riscos (OVIATT; MCDOUGALL, 2005;FELZENSZTEIN et al, 2015). Como tal, o nível de propensão ao risco dos decisores em uma PME tende a afetar o caminho e a intensidade de progresso de exportação.…”
Section: Relevância Do Temaunclassified
“…Vários estudos apontam que o processo de internacionalização de PME recebe a influência de diversos fatores internos e externos, sendo que o decisor é o principal responsável pela elaboração das estratégias a serem adotadas pela PME (FELZENSZTEIN et al, 2015;JAVALGI;TODD, 2011;OMRI;BECUWE, 2014). Entretanto, é possível que o decisor possua algumas características gerenciais, tais como o capital humano, o capital social, propensão ao risco e percepção de risco, que variam de níveis, podendo influenciar a tomada de decisão no sentido de internacionalizar a PME.…”
Section: Objetivos Do Estudounclassified
See 2 more Smart Citations